2016
DOI: 10.3329/brj.v19i2.28166
|View full text |Cite
|
Sign up to set email alerts
|

Rice Response to Nitrogen in Tidal Flooded Non-saline Soil

Abstract: CORRECTION: Due to a number of formatting and layout issues, the PDF of this paper was replaced on 10th October 2016. The page numbers of this article have changed from 62-67 to 65-70. The name of the fifth author has changed from US Naher to UA Naher.Cultivation of modern varieties (MV) of rice in the coastal non-saline soils of the Asian countries is increasing. Nitrogen (N) deficiency is one of the most nutritional disorders for lowland rice production in Bangladesh. N management recommendation for MV rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In Boro season, most of the AE N values were above the Doberman standard with different N rates, while in T. Aman season, the AE N values of BRRI dhan75 were below the standard (Table 5). Islam et al (2015) reported 16-36 kg kg −1 AE N in Boro rice, while Hussain et al (2016) found AE N between 0.52 and 17 kg kg −1 in T. Aman rice which supports our results. Our study also indicates that AE N decreased with the increase of N inputs.…”
Section: Nitrogen Uptake and Use Efficiencysupporting
confidence: 91%
“…In Boro season, most of the AE N values were above the Doberman standard with different N rates, while in T. Aman season, the AE N values of BRRI dhan75 were below the standard (Table 5). Islam et al (2015) reported 16-36 kg kg −1 AE N in Boro rice, while Hussain et al (2016) found AE N between 0.52 and 17 kg kg −1 in T. Aman rice which supports our results. Our study also indicates that AE N decreased with the increase of N inputs.…”
Section: Nitrogen Uptake and Use Efficiencysupporting
confidence: 91%
“…PE also decreased with increasing N application over N100 and showed that yield increased per kilogram N accumulated in rice plant was decreased with increasing N application greater than N100. AE was 16–36 in Boro rice ( Islam et al., 2015 ) and 0.52–17 in T. Aman rice ( Hussain et al., 2016 ). AE significantly increased with increasing N levels up to 165 kg N ha −1 and decreased with further uplift in N application in some recently released Egyptian rice varieties ( Ghoneim and Osman, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yesuf and Balcha (2014) also reported similar findings. Sharma and Mittra (1990), Paikaray et al (2001), Jahan et al (2014), Islam et al (2015), and Hussain et al (2016) reported that the use of an optimum dose of N might have helped for good vegetative growth and root system, which increased the higher N uptake by plants and hence increased yield and yield components of rice. The combination effect of variety and different N rate applications had a non-significant influence on NUP at different growth stages of the three varieties of Aus rice (Table 3).…”
Section: Nitrogen Uptake By Plants During Growth Stagementioning
confidence: 99%